As vozes da infância: narrativas e estórias das crianças em interações em uma Umei de Belo Horizonte - Priscilla Moura Bastos (2016)
Oral language is one of the dimensions that constitute the formation of social subjects. It is a process that begins in early childhood with the appropriation of language and the assignment of meanings to the world. Besides its representative function, language is also a form of communication and social interaction. The first experiments with language enable children to integrate themselves into the symbolic and cultural universe. Initially, children use a kind of language that is not yet conditioned to linguistic conventions and this is shown, for example, in the playfulness that permeates the games, in the childhood cultures that children produce in the interaction with their peers and in the narratives that they create to tell or reinvent their experiences. In this sense, children do not only express a thought with words, they learn to play with the polysemy of language. This research is aimed at analyzing childrens oral language taking for granted the narratives and stories that they tell in their interactions in a Municipal Unit of Childhood Education from Belo Horizonte. The research is qualitative and is structured in a partnership with the children. The methodological tools used in this research are the participant observation, the notes in the field journal, and the photographs and the footages that show activities that demonstrate oral language. This partnership enabled the interaction with the children, which is essential to understand their ways of narrating and telling their stories. We take as a theoretical framework the studies of Corsaro (2011), Sarmento and Gouvêa (2009), Benjamin (1994; 2002; 2013), and Vygotsky (2014). The research also includes a brief study of the history of early childhood education in relation to the recognition of children as subjects of law. Finally, as a requirement of the Professional Master's Program in Education and Teaching, we produced, from the footages and photographs taken with the permission of the families, teachers, and with the consent of the children, a short video titled What the children tell us about a visit to an art exhibition.